A Sense of Belonging in Online Post-Traditional Students: What Matters? - Xu, Li; Brown, Sheena (Online Learning, 2024)
Online education has experienced a rapid growth and continued to grow, which is driven by the advances in information and communication technologies that facilitate effective interactions both within and outside the online classroom in high education. Despite these advancements, post-traditional students, characterized by their diverse and complex identities, face unique challenges in forming connections within online learning environments. This research focuses on sense of belonging, which is crucial for promoting and consolidating online learning experiences. For post-traditional students, little is currently known about the extent to which they feel a sense of belonging and the factors that influence it. In this research study, we surveyed a sample of online post-traditional learners and used a mixed-methods approach to examine how they feel accepted and valued and how their identities such as academic program, gender, and ethnicity are related to belonging. Our findings indicate that post-traditional learners report an overall moderate level of belonging, with university support, acceptance, and meaningful relationships with faculty and staff being pivotal. Our research did not find significant differences between students in different academic programs or gender groups. However, Hispanic students reported a higher sense of belonging, which can be contextualized within the framework of our university’s designation as a Hispanic-Serving Institution (HSI). By pinpointing the critical and negligible factors affecting sense of belonging, this study provides a comprehensive set of actionable strategies to cultivate a more engaging and supportive online learning environment.